Female images in Karachay-Balkar historical-heroic songs - Leyla S., Gergokova (Kavkazologiya, 2024)
This article focuses on the study of one of the little-studied areas of oral folklore – Karachay-Balkar historical and heroic songs. The object of the study was female images found in folk poetry of this ethnic group. In the analysis of gender aspects of ancient poetic texts, through an integrated approach to the study, the article used comparative and contrastive and historical and typological research methods. The theoretical basis for the research was the works of domestic and national scientists studying various issues of oral poetry. Because of a continuous sample from different folklore collections, historical and heroic songs were analyzed, during the analysis of which the primary attention is paid to the internal and social qualities of the character of female characters, their figurative system. These images are divided and presented as active and passive heroes. It should be highlighted that passive images, as opposed to active ones, which are the main charac-ters in the investigated works, play a minor part in plot development. The article provides an as-sessment of the social model of behavior of female characters in different life circumstances. The research concludes that future investigation of the gender issue in historical-heroic songs would address existing gaps in the scientific fund and contribute to the conduct of comparative research on this topic.